Sexual Harassment in Our Schools; and How to Stop Sexual Harassment in Our Schools [book reviews] - Janette Flores-Diaz; D. Mark Tuckett (Educational Considerations, 1995)
Book reviews of: Sexual Harassment in Our Schools: What Parents and Teachers Need to Know to Spot It and Stop It, by Robert J. Shoop and Jack W. Hayhow, Jr. ; and How to Stop Sexual Harassment in Our Schools: A Handbook and Curriculum Guide for Administrators and Teachers, by Robert J. Shoop and Debra J. Edwards.